88. The sympathetic skin response as a predictor of recovery of ulnar nerve lesion at wrist. Issue 12 (December 2017) - Magistroni, E.; Devigili, G.; Milani, P.; Massazza, G.; Eleopra, R.
Abstract : The aim of the study was to evaluate, in the ulnar nerve injuries, distally to the elbow, the role of monitoring the function of sudomotor fibers assessed by Sympathetic Skin Response (SSR) during recovery after surgical treatment and rehabilitation. We recruited 31 patients admitted for rehabilitation after traumatic wrist injury with ulnar nerve and artery lesions. Patients with other nerves or artery involved were excluded. All patients underwent surgical primary nerve repair within 72 h and the same rehabilitative program. Everyone performed the sensory and motor nerve conduction studies, the needle EMG, the SSR evoked by deep breathing, acoustic and electrical stimuli, recorded bilaterally at the ulnar (uln-SSR) and the median (med-SSR) sides of the hand. All the tests were performed at one (T0), three (T1), six (T2), twelve (T3) months from the injury. Results. At T0, the uln-SSRs at the affected site were absence in all, while med-SSR was present. At T1, uln-SSR appeared with low amplitude, while the distal ulnar cMAP was still not recordable. At T2 the amplitude of uln-SSR improved significantly, and it preceded the ulnar cMAP recovery. Conclusion. We suggest to monitor the SSR as a better predictor in ulnar nerve injuries at wrist.